Politeness of Speaking Introduced in Conversation Texts in MTs English Textbook Grade VII - Nuha, Ulin (Institut Agama Islam Negeri Kudus, 2020)
This study analyzes the conversation texts found in grade VII English textbook entitled “EOS English on Sky 1”. This study focuses on the issues: social contextual factors approach which analyzes the participants in the interaction and the communicative situation, and politeness which analyzes the respect that an individual has for him or herself and maintains the